A review of anticaking agents in the realm of digital food printing - MALIYIL, SONY JOSEPH; Prabeesh E.; Blue Wings, Joseph Markose; Teddy N Alias (Indonesian Nutrition Association, 2024)
Background: Various food additives including anticaking agents have been in use since the second half of last century and digital printing of food is in practice. Concerns on food borne disease transmission following COVID-19 accelerated research in the direction of 3D printing. Objective: 3D printing of food depends on the rheological property of the dough. In addition to enhance the flow, anticaking agents which have other properties too can be exploited in 3D printing. Artificial intelligence (AI) assisted printing, targeting sustainability and customizability is in progress which needs data of food additives. The review has been done to consolidate data of the authorised anticaking agents used in food. Methods:Using terms according to the criteria, a literature search was conducted with the data bases: Google Scholar, PubMed, ScienceDirect and Web of Science. Literature for full text analysis were selected from abstracts of 420 papers and books resulted on search, eliminating those prior to 2014, which were out of scope of the journal Results:Consolidated literature about the anticaking agents authorised in Codex, is made discussing the deficiencies in the existing evaluation and highlighting the use of anticaking agents in 3D food printing. Promising application of the anticaking agents in AI assisted food printing has been observed. Conclusion:This review being the first of its kind, consolidates the data of the anticaking agents including the current utility in 3D printing. It may instigate further research in this regard.